The Impact of Governance Structure on Firm Performance: Evidence from Japanese Local Mixed Enterprises - Tomoyasu Tanaka; Takao Goto (European Regional Science Association (ERSA), 2011)
In Japan, many local mixed enterprises owned and operated jointly by local governments and private sectors had been established from the late 1980's to the early 1990's in order to provide public services more efficiently. At present, in Japan, many local mixed enterprises are confronted with a serial fiscal crisis. In 2007, the national government enacted the Local Public Finance Reconstruction Law and started to lead local mixed enterprises and local governments to achieve fiscal soundness. In addition to local governments, mixed enterprises have to make an effort to operate more efficiently. However, we believe that local mixed enterprises lack the incentives to manage more efficiently because of the governance structure. Firstly, as local mixed enterprises are owned by local governments, they can procure government-guaranteed funds and are able to raise capital more easily. Also, if business conditions of enterprises worsen, local governments give subsidies to bail out ailing enterprises. Managers do not have to worry about going bankrupt and might continue to carry out inefficient projects. Secondly, if managers are from local governments, or if the majority of the board members are local government officials, they might supply services without putting stress on profit. Therefore, it is possible that the governance structure of local mixed enterprises is the important factor that determines their performance. In this paper, we study the link between the performance and the governance structure in local mixed enterprises.
Keywords: 330